Penggunaan Metode TTW (Think-Talk-Write) terhadap Keterampilan Menulis Cerpen - Salsabila; Lilis Rahmawati; Nazifa Sukri; Siti Fadillah; Sry Apfani (CARONG: Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to examine the effect of the Think-Talk-Write (TTW) method on students' short story writing skills through a literature review approach. Short story writing is a crucial aspect of Indonesian language learning as it involves creative thinking, logical narrative structure, and expressive language use. However, in practice, students often face difficulties during the prewriting stage, such as generating ideas, developing characters, and constructing conflicts and settings. The TTW method offers a structured approach involving individual thinking, group discussion, and directed writing, thereby promoting a more systematic development of writing skills. Based on the synthesis of various scholarly sources, the TTW method has been proven effective in improving students’ writing quality in terms of structure, content, and language use. Intrinsic elements of short stories such as theme, plot, character, setting, and point of view show significant improvement when taught using the TTW method. This study concludes that the TTW method can serve as a relevant and practical strategy for teachers to enhance students’ short story writing skills.